The Role of Asset Management, Operational Efficiency and Expense Management on the Performance of Commercial Banks in Bangladesh - Chowdhury, A. N. M. Minhajul Haque; Akhtar, Rafia (Asian Business Review, 2017)
The performance of the banks depends on some bank-specific factors. This paper set out to investigate the influence of asset management, operational efficiency and expense management on the financial performance of five commercial banks in Bangladesh for the period of 2011-2015. Descriptive statistics, correlation, and regression techniques were applied to find out the ultimate results. The empirical study suggested that operational efficiency had a positive effect on the dependent variables return on asset (ROA), and return on equity (ROE), but expense management was negatively related to the both indicators. On the other hand, asset management was positively related to ROA but negatively related to ROE. In addition, the regression results summed up that the changes in the performance of commercial banks could explain by bank-specific factors selected for the study.
Keywords: Return on equity; return on asset; asset management; commercial Banks; operational efficiency; expense management